Big Data and Digital Aesthetic, Arts and Cultural Education: Hot Spots of Current Quantitative Research - Christ, Alexander; Penthin, Marcus; Kröner, Stephan (Social Science Computer Review, 2021)
Systematic reviews are the method of choice to synthesize research evidence. To identify main topics (so-called hot spots) relevant to large corpora of original publications in need of a synthesis, one must address the “three Vs” of big data (volume, velocity, and variety), especially in loosely defined or fragmented disciplines. For this purpose, text mining and predictive modeling are very helpful. Thus, we applied these methods to a compilation of documents related to digitalization in aesthetic, arts, and cultural education, as a prototypical, loosely defined, fragmented discipline, and particularly to quantitative research within it (QRD-ACE). By broadly querying the abstract and citation database Scopus with terms indicative of QRD-ACE, we identified a corpus of N = 55,553 publications for the years 2013–2017. As the result of an iterative approach of text mining, priority screening, and predictive modeling, we identified n = 8,304 potentially relevant publications of which n = 1,666 were included after priority screening. Analysis of the subject distribution of the included publications revealed video games as a first hot spot of QRD-ACE. Topic modeling resulted in aesthetics and cultural activities on social media as a second hot spot, related to 4 of k = 8 identified topics. This way, we were able to identify current hot spots of QRD-ACE by screening less than 15% of the corpus. We discuss implications for harnessing text mining, predictive modeling, and priority screening in future research syntheses and avenues for future original research on QRD-ACE.<br
Keywords: big data; text mining; aesthetic; arts; cultural education; digitalization; predictive modeling

Children’s and adolescents’ engagement with music and the potential for (digital) empowerment processes: A text-mining-supported scoping review - Smolarczyk, Kathrin; Birnbaum, Lisa; Christ, Alexander; Kröner, Stephan (Psychology of Music, 2024)
Extracurricular and out-of-school engagement with music is often associated with positive effects for musical goals while also holding potential for developmental and empowerment processes. The COVID-19 pandemic has highlighted the importance and the potential of digital technologies for facilitating musical engagement. The emergence of digitally transformed musicking has added complexity to the already multifaceted and complex field of research on non-formal musical engagement. Thus, the aims of this text-mining-supported scoping review are (1) to map and describe the underlying research topics in the field of children’s and adolescents’ musical engagement, (2) to explore potential for empowerment processes, and (3) to identify the extent to which digital aspects emerge. Based on N = 624 articles, a topic-modeling procedure yielded k = 10 topics covering cognitive, emotional and attitudinal, youth cultural and digital aspects. Among these, one predominantly digital topic comprised studies on the production and consumption of music. Implications for the potential for empowerment can be drawn from studies that focus on youth cultural aspects, such as hip-hop culture and digital aspects. Limitations and implications for further research are discussed, including how to transfer these findings and how new technologies can further enhance music-making and creation.
CRIS-Team Scopus Importer:2024-05-10
Keywords: empowerment; music; non formal education; scoping review; text-mining

Detrimental effects of an economic crisis on student cognitive achievement – A natural experiment from Palestine - Bisharat, Khaled; Christ, Alexander; Kröner, Stephan (Intelligence, 2020)
In this study, we investigated the differential effect of regional economic prosperity on mean student cognitive achievement by analysing data from a “natural experiment” in Palestine. Its main regions, Gaza and the West Bank, inhabited by a population sharing history, culture and gene pool, were only recently separated, yet distinctively affected by geopolitical events. The “experimental group”, living in Gaza, suffered from an enduring politico-economic crisis treatment, while the “control group”, inhabitants of the West Bank, was exposed to a much shorter and milder crisis. As a manipulation check, we used economic data reported by Etkes and Zimring (2015), who uncovered a severe and lasting decrease in household welfare and labour productivity in Gaza. As dependent variables, we used achievement scores of TIMSS maths and science students, which displayed only negligible pro-West Bank, pre-crisis differences (maths: Cohen's d = −0.04; t = −0.56; science: d = 0.11; t = 1.48). This margin grew during the crisis (maths: d = 0.17; t = 2.65; science: d = 0.26; t = 4.25) and even more so in the post-crisis phase (maths: d = 0.38; t = 5.09; science: d = 0.46; t = 6.76). Our results corroborate correlational evidence for economic effects on cognitive achievement (cf. Hunt, 2012). Relying on a natural experiment, we were able to rule out genetic effects and highlight the impact of the environment on students' academic achievements. Limitations of the design and implications for further studies on regional differences in cognitive achievement are discussed.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Economic prosperity; Natural experiment; Palestine; Student cognitive achievement

Does Teachers’ Spirituality Make a Difference? The Explanatory Value of Spirituality and Religiosity for Teachers’ Professional Beliefs on Teaching and Learning - Penthin, Marcus; Christ, Alexander; Kröner, Stephan; Pirner, Manfred; Scheunpflug, Annette (Religion & Education, 2023)
While it is often theoretically presumed that religious and spiritual beliefs are important determinants for teachers’ professional thinking and acting, there is only scarce empirical evidence of this. Using structural equation modeling to explain professional beliefs about teaching and learning among N = 1,441 German schoolteachers, our study yielded virtually no explanatory value for religiosity, but certainly one for non-transcendet spiritual beliefs as predictors. Our research results differ from findings in some studies from the U.S. that showed substantial correlations between teachers’ religious and professional beliefs. Some possible reasons are reflected in the discussion section.Highlights Teachers’ religiosity and spirituality are weakly related to professional beliefs. “Connectedness with oneself” explains the sense of professional self-efficacy. “Connectedness with others” explains an idealistic self-concept. “Connectedness with others” explains student-centered attitudes. Control variables/factors explain teachers’ professional beliefs to some extent.
CRIS-Team Scopus Importer:2023-04-07
Keywords: teacher beliefs; religiosity; religious education; spirituality; self-efficacy

Forschungssynthesen zur Digitalisierung in der kulturellen Bildung - Kröner, Stephan; Penthin, Marcus; Christ, Alexander (Forschung zur Digitalisierung in der Kulturellen Bildung, 2019)
Im hier vorgestellten Teil des Metaprojekts zum Förderschwerpunkt Forschung zur Digitalisierung in der kulturellen Bildung (DikuBi) steht die Synthese quantitativ-empirischer Forschung im Fokus. Forschungssynthesen gewinnen – ausgehend von der Bewährung dieses Ansatzes in anderen Disziplinen – auch in der Bildungsforschung an Bedeutung. Sie sind geeignet, um den internationalen Forschungsstand disziplinübergreifend sichtbar zu machen. Es gilt daher, derartige systematische Übersichtsarbeiten auch zu Forschungsschwerpunkten im Feld der Digitalisierung in der kulturellen Bildung zu erstellen. Hierzu wird zunächst eine breit angelegte Recherche in diesem Feld durchgeführt und deren Ergebnisse werden inhaltsanalytisch kategorisiert. Davon ausgehend werden thematische Schwerpunkte der bisherigen Forschung identifiziert und quantitative Synthesen (Metaanalysen) zu diesen Schwerpunkten erstellt. Potentiell relevante Studien werden nur dann tatsächlich einbezogen, wenn sie den Mindestanforderungen an Qualität und Evidenzgrad entsprechen. Ausgehend von den so erstellten Forschungssynthesen sollen schließlich Desiderate zu Design und Ausrichtung künftiger Studien benannt und Perspektiven für die weitere Forschung aufgezeigt werden. Außerdem werden Empfehlungen erarbeitet, wie die Forschung zur Digitalisierung in der kulturellen Bildung enger vernetzt und ihre internationale Sichtbarkeit erhöht werden kann.
Keywords: kulturelle Bildung; Digitalisierung; Meta-Analyse; Literaturüberblick; Tertiäres Review; Forschungssynthese

Multiple complex problem-solving scenarios: The incremental validity of ability self-concept beyond reasoning in adults - Christ, Alexander; Becker, Nicolas; Kröner, Stephan (Intelligence, 2020)
Keywords: Computer simulation; Self-concept; Problem-solving; Reasoning; Cps

Religiöse und berufsbezogene Überzeugungen von Lehrkräften – zentrale Befunde aus dem empirisch-quantitativen DFG-Projekt „RebeL“ - Scheunpflug, Annette; Pirner, Manfred; Kröner, Stephan; Penthin, Marcus; Christ, Alexander (Zeitschrift für Pädagogik und Theologie, 2024)
This article presents the central findings of the study “Religious and Professional Beliefs of Schoolteachers (RebeL)”. A quantitative survey was conducted with N = 1,441 teachers in Bavaria, North Rhine-Westphalia and Saxony, including 408 teachers with religious education as a subject, with regard to relationships between their religious and professional beliefs as well as moderating contextual and subjective factors. The results of multivariate analyses showed that the teachers’ professional beliefs are largely independent of most facets of religious-spiritual beliefs; substantial relationships were mainly found for the spirituality facet “Connectedness with others” and the religious and worldview tolerance of the teachers. This finding is discussed in terms of its significance for religious education. In diesem Beitrag werden die zentralen Befunde der Studie „Religiöse und berufsbezogene Überzeugungen von Lehrkräften (RebeL)“ vorgestellt. Untersucht wurden N = 1.441 Lehrkräfte in Bayern, Nordrhein-Westfalen und Sachsen, darunter auch 408 Lehrkräfte mit Religion als Unterrichtsfach, hinsichtlich der Zusammenhänge zwischen ihren religiösen und berufsbezogenen Überzeugungen sowie moderierenden kontextuellen und subjektiven Faktoren. Es zeigte sich in multivariaten Analysen, dass die berufsbezogenen Überzeugungen der Lehrkräfte von den meisten Facetten der religiös-spirituellen Überzeugungen weitgehend unabhängig sind; substantielle Zusammenhänge ergaben sich überwiegend für die Spiritualitätsfacette „Verbundenheit mit anderen“ sowie die religiös-weltanschauliche Toleranz der Lehrkräfte. Dieser Befund wird in seiner Bedeutung für die Religionspädagogik diskutiert.<br
Keywords: berufsbezogene Überzeugungen; religiöse Überzeugungen; Religiosität; Spiritualität; Lehrkräfteforschung teacher beliefs; teachers’ religious beliefs; religiosity; spirituality; teacher research

Schwerpunktthemen der quantitativ-empirischen Forschung mit Bezug zur Digitalisierung in der kulturellen Bildung: Eine kartierende Forschungssynthese - Christ, Alexander; Smolarczyk, Kathrin; Kröner, Stephan (Zeitschrift für Erziehungswissenschaft, 2023)
In the context of the digital transformation, cultural activities have also changed. “Classical” activities have been digitally transformed, and new, genuinely digital activities have emerged. Many studies from various disciplines refer to this, which have not yet been adequately processed through research syntheses. Mapping reviews are suitable for providing an overview of the hot topics and desiderata of quantitative-empirical research at the intersection of digitization and cultural participation. In view of the large number of articles to be included, text mining including prioritized screening via predictive modelling is helpful. After screening n = 8500 potentially relevant papers from a database of n > 250,000 papers via predictive modelling, n = 3846 papers were included and mapped via topic modelling according to the investigated facets of cultural activities and overarching research themes. For the facets of cultural activities, a hot topic on video games was identified. For the overarching research themes, a variety of different topics emerged such as formal education in schools or motivation and flow. Regarding the methods chosen, it is discussed that these foci and desiderata across heterogeneous themes pave the way for topic-specific research syntheses as well as for further original research on the desiderata. Implications for the further development of the applied methods are discussed.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Cultural education; Digitalization; Research synthesis; Text mining; Topic modeling

Stichwort: Digitalisierung in der kulturell-ästhetischen Bildung – eine konfigurierende Forschungssynthese - Kröner, Stephan; Christ, Alexander; Penthin, Marcus (Zeitschrift für Erziehungswissenschaft, 2021)
Digitalisierung verändert zunehmend die kulturelle Bildung. Im Zuge des technologischen Fortschritts werden auch soziale Interaktionen, ästhetische Erfahrungen und Ausdrucksformen transformiert. In diesem Beitrag wird über eine konfigurierende Forschungssynthese zur Kartierung des sich entwickelnden Forschungsfeldes zur Digitalisierung in der kulturellen Bildung berichtet. Dazu wurden im Fachportal Pädagogik und in Scopus empirisch ausgerichtete Originalarbeiten mit explizitem Bezug zu Digitalisierung in der kulturellen Bildung identifiziert und nach formalen sowie inhaltlichen Kriterien kategorisiert. Inhaltlich wird ein Schwerpunkt in den bildenden Künsten deutlich. Arbeiten zu aktuellen Entwicklungen wie Digital Making und Virtual Reality sind jedoch selten. Ein Großteil der vorliegenden Arbeiten fokussiert auf formale Bildungsprozesse. Im Zentrum steht oft die Frage nach Determinanten von Kompetenzerwerb, Interesse und Motivation. Resultierende Evidenz wird jedoch häufig begrenzt durch schwache Designs, naive Vergleiche analog/digital und unterausgewertete Datensätze. Diskutiert wird, wie diese Desiderate in künftiger quantitativer wie qualitativer Forschung adressiert werden könne
Keywords: Digitalisierung; Forschungssynthese; Kulturelle; Ästhetische Bildung; Kulturelle Aktivitäten

Two decades of research synthesis on digital cultural education: A tertiary review - Christ, Alexander; Penthin, Marcus; Kröner, Stephan (Journal for Educational Research Online, 2025)
Digitalization fundamentally increased access to receptive cultural participation for a broad audience and created new opportunities for active participation such as video games and social media. While studies on classical cultural activities often use qualitative designs for examining positive effects, studies on digital cultural activities tend to use quantitative designs and focus on negative effects. In order to obtain a substantiated and comprehensive overview, we subjected available published research syntheses on effects of digital cultural activities to a tertiary review including mapping their topics and analysing the research methods applied. To accomplish this goal, we screened N = 5.880 Scopus raw hits resulting in n = 65 research syntheses that met our inclusion criteria. Of all included syntheses, n = 22 were systematic literature reviews and n = 43 meta-analyses. The cultural facet investigated most frequently was video games (n = 36), classical facets were synthesized less frequently. While n = 19 syntheses focused on online interactions, n = 4 syntheses studied activities such as VR requiring special hardware. The included syntheses heavily focused on the research topics “learning” (n = 29) and “subjective well-being and mental health” (n = 26), while articles on “entertainment/engagement” were synthesized by n = 13 reviews. Most included syntheses on video games and social media focused on negative effects such as addictive or aggressive behaviour, positive effects of those activities were synthesized less frequently. The included syntheses also only rarely synthesized qualitative studies. Implications of those desiderata for systematic reviews and empirical original research on D-ACE are discusse
Keywords: arts education; digitalization; cultural education; research synthesis; tertiary review

Verortung der Förderrichtlinie DiKuBi und ihrer Vorhaben im Kontext der internationalen Forschung zur Digitalisierung in der kulturellen Bildung. In: Jörissen, B., Kröner, S., Birnbaum, L., Krämer, F. & Schmiedl, F. (2023). Digitalisierung in der kulturellen Bildung: Interdisziplinäre Perspektiven für ein Feld im Aufbruch. - Christ, Alexander; Birnbaum, Lisa; Smolarczyk, Kathrin; Kröner, Stephan (Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch, 2023)
Welche Konsequenzen und Potenziale bringt die digitale Transformation für die kulturelle Bildung mit sich? Antworten auf diese Frage bietet der vorliegende Band in Form einer Übersicht über Forschungsergebnisse aus dem BMBF-Förderschwerpunkt „Forschung zur Digitalisierung in der kulturellen Bildung“. Über mehrere Jahre hinweg haben darin 13 Verbund- und Einzelprojekte in ganz Deutschland zu digitalen Phänomenen in der kulturellen Bildung geforscht: zu Musik, Literatur, Tanz, Performance, bildender Kunst und darüber hinaus. Die Forschungsvorhaben zeichnen sich durch eine große Perspektivenvielfalt aus: Neben Erziehungswissenschaft und Bildungsforschung sind spezifische Sparten der kulturellen Bildung und weitere geisteswissenschaftliche Fächer ebenso vertreten wie die wie die Informatik. Zudem hat ein Metavorhaben qualitativ-metatheoretische Perspektiven entwickelt sowie Forschungssynthesen zur Digitalisierung der kulturellen Bildung insgesamt und zum digitalen Wandel einzelner kultureller Aktivitäten erarbeitet, teils unter Verwendung von Big-Data-Methoden. Die im Buch gebündelten Ergebnisse stellen eine wertvolle Ressource für Handelnde in Forschung, Kulturpädagogik und Politik dar, indem sie es ermöglichen, sich einen Überblick über das Innovationspotenzial zu verschaffen, welches sich aus der digitalen Transformation von kultureller Bildung ebenso ergibt wie aus ihrer Erforschung. (DIPF/Orig.)<br
Keywords: Kulturelle Bildung; Digitalisierung; Digitale Medien; Jugendkultur; Forschung; Bildung; Bildungsangebot; Inklusion; Mehrfachbehinderung; Partizipation; Anwendung; Soziales Netzwerk; Erwachsenenbildung; Lernumgebung; Musikunterricht; Musik; Musizieren; Musikwissenschaft; Medienpädagogik; Lernprozess; Kunstpädagogik; Ästhetische Bildung; Rezension; Bewertung; Bildungsprozess; Empirische Forschung; Deutschland

Zusammenhänge zwischen religiös-spirituellen und berufsethischen Überzeugungen von Lehrkräften - Penthin, Marcus; Christ, Alexander; Kröner, Stephan; Pirner, Manfred; Scheunpflug, Annette (Zeitschrift für Erziehungswissenschaft, 2022)
Ob persönliche religiös-weltanschauliche Überzeugungen von Lehrkräften deren berufliches Denken und Handeln beeinflussen und ob sie es beeinflussen sollten, ist immer wieder Gegenstand öffentlicher Diskussionen. Angesichts eines dahingehend unbefriedigenden Forschungsstands, insbesondere im europäischen Kontext, wurde der Erklärungswert von Religiosität und Spiritualität für die berufsethischen Überzeugungen von N = 1441 Lehrkräften an deutschen Schulen untersucht. Entgegen unseren präregistrierten Hypothesen klärten in Strukturgleichungsmodellen weder religiöse Überzeugungen noch religiöse Toleranz nennenswerte Varianz in verschiedenen Aspekten des Berufsethos auf. Ein größerer Erklärungswert ergab sich bei vergleichbaren Analysen für die spirituellen Überzeugungen, jedoch weniger für deren transzendente Aspekte als für die Dimension der „Verbundenheit mit anderen“. Diskutiert wird, dass es offensichtlich weniger die religiösen und transzendent-spirituellen Überzeugungen der Lehrkräfte sind, die einen Effekt auf ihre berufsethischen Überzeugungen haben, als eine damit tendenziell einhergehende altruistische Haltun
Keywords: Religiosität; Spiritualität; Lehrkräfte; Berufsbezogene Überzeugungen